Cobalt(II) coordination polymers as anodes for lithium-ion batteries with enhanced capacity and cycling stability. Issue 8 (August 2018) - Luo, Yumei; Sun, Lixian; Xu, Fen; Wei, Siyue; Wang, Qingyong; Peng, Hongliang; Chen, Chonglin
Abstract: Coordination polymer Co-btca (H4 btca = 1, 2, 4, 5-benzenetetracarboxylic acid) was synthesized using a simply hydrothermal method. In particular, the as-prepared Co-btca was applied as an anode material for lithium-ion battery for the first time. Single crystal X-ray diffraction results indicated that the as-prepared Co-btca displayed unique layer structure, which was beneficial to transport Li ions and electrons. Also, owing to the porous structure and appropriate specific surface area, Co-btca electrode delivered a reversible capacity of 801.3 mA h/g after 50 cycles at a current density of 200 mA/g. The reversible capacity of 773.9 mA h/g was maintained after 200 cycles at a current density of 500 mA/g, exhibiting enhanced cycle stability. It also showed improved rate performance, making it a promising anode material and a new choice for lithium-ion batteries.